Hubungan Pola Asuh dengan Status Gizi pada Anak Balita di Desa Sidorejo, Wonogiri - Az'zahro Syal Sabillah; Tri Susilowati (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Nutritional problems among toddlers remain a serious challenge in various regions. Globally, the prevalence of stunting reaches 22.3%, wasting 6.8%, and overweight 5.6%. In Indonesia, 6.4% of toddlers experience undernutrition, and 4.7% are at risk of being overweight. In Wonogiri, there are 5,094 toddlers with underweight, 4,590 with stunting, and 265 with severe malnutrition, with the highest number of cases found in Tirtomoyo Subdistrict.This study aims to determine the relationship between parenting styles and the nutritional status of toddlers in Sidorejo Village, Wonogiri. The research employed a quantitative approach with a cross-sectional design. Data were collected using the Parenting Styles and Dimensions Questionnaire-Short Form (PSDQ), anthropometric measurements based on the weight-for-height index, and the Maternal and Child Health (MCH) book. The population consisted of all toddlers and their mothers in Sidorejo Village, totaling 301 individuals. A Proportionate Stratified Random Sampling technique was used to select 75 respondents. Data analysis was conducted using the Spearman Rank correlation test.The results showed that 50 mothers (66.7%) applied a democratic parenting style, and 45 toddlers (60%) had normal nutritional status. A significant relationship was found between parenting style and the nutritional status of toddlers (p = 0.000; p < 0.05), with a correlation coefficient of 0.418, indicating a moderate relationship. Based on the results obtained, it is concluded that there is a relationship between parenting style and the nutritional status of toddlers in Sidorejo Village, Wonogiri.